Spacing and places arrangements: a study of the identity symbols of the Moto Club ‘Children of Freedom’ and their representations - Rocha, Eliana do Pilar (Open Science Journal, 2021)
The article is the result of an ethnography carried out on a motorcycle club located in the city of Curitiba, Brazil, called the Brotherhood Children of Freedom, and seeks to understand how the members of the motorcycle club construct the category of place in different micro spaces through their greater symbols, such as the brotherhood headquarters, the badge in their vests and the trips through the roads under formation. The city is considered as a field of analysis, from the overlapping spaces and plurality individual group. In this context, it describes the identity constructions among the Brotherhood's members, their obligations and restrictions in new arrangements related to those appropriate spaces and transformed into place. It also shows how, in relations with others inside or outside the city, spaces of different scales are appropriate by the members of the Brotherhood by means of their symbols, values, beliefs and identity, to which systems of significance are attributed, such as the very notion of belonging and tradition of the Brotherhood Children of Freedom.